2023
DOI: 10.1039/d3cp03707j
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study on the ORR electrocatalytic activity of axial ligand modified cobalt polyphthalocyanine

Guilin Wang,
Xiaoli Yang,
Ruiying Wang
et al.

Abstract: In this work, the catalytic activity of the oxygen reduction reaction (ORR) of cobalt polyphthalocyanine whose central Co atom coordinated at the axial position by the ligands (L= -F, -OH,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…The Mayer bond order was defined by the density matrix P and the overlapping matrix S, which also was an useful tool for chemical bonding analysis. [ 16 ] The ORR began with *OOH (the first ORR intermediate) occupying the catalytic site, and the entire ORR cycle finished as soon as *OH (the final ORR intermediate) was released. Due to orbital interactions, HfN 4 O exhibits a higher strength of *OOH adsorption (1.12) compared to HfN 4 (1.03) in favor of the start of ORR.…”
Section: Resultsmentioning
confidence: 99%
“…The Mayer bond order was defined by the density matrix P and the overlapping matrix S, which also was an useful tool for chemical bonding analysis. [ 16 ] The ORR began with *OOH (the first ORR intermediate) occupying the catalytic site, and the entire ORR cycle finished as soon as *OH (the final ORR intermediate) was released. Due to orbital interactions, HfN 4 O exhibits a higher strength of *OOH adsorption (1.12) compared to HfN 4 (1.03) in favor of the start of ORR.…”
Section: Resultsmentioning
confidence: 99%
“…The modified ligands of F, Cl, and CH 3 coordinated axially on Fe–N–C catalysts were found to reduce the orbital hybridization between Fe and *OH and hence promote *OH desorption by improving ORR performance. CO modified on the Rh site could stabilize *OOH intermediates and promote the two-electron and four-electron ORR processes . The axial NO, HCO 3 , CH 3 , and CN coordination optimized the electronic structure of Fe, which improved U L to 0.72, 0.82, 0.69, and 0.86 V from the original 0.56 V of the pristine Fe–N–C catalyst. These results indicated that axial ligand engineering is an effective measurement for affecting ORR activities in metal–nitrogen-carbon materials.…”
Section: Introductionmentioning
confidence: 96%
“…59 Wang et al reported that cobalt polyphthalocyanine with an axially coordinated azide showed much better catalytic performance for the ORR than that of pristine cobalt polyphthalocyanine. 71…”
Section: Introductionmentioning
confidence: 99%